The Role of Humanistic Academic Supervision in Improving the Quality of Teaching and Learning in SLB At-Turmudzi 1 Malangbong - Rosa, Ade Tuti; Nurdiana, Irfan Intan; Purnamasari, Feny Afifah; Saniputri, Regina Maheswari; Rahayu, Diah Daniswara (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study examines the role of humanistic academic supervision in improving the quality of learning at SLB At-Turmudzi 1 Malangbong, Garut. Although inclusive education is widely discussed, most supervision models are still procedural and evaluative in nature, ignoring the reflective and emotional needs of teachers. This study aims to fill this gap by exploring how humanistic supervision supports professional growth and inclusive practices.Method – Using a descriptive qualitative approach, data were collected through in-depth observations, semi-structured interviews with the principal and ten special education teachers, and document analysis. Data were analyzed using the Miles and Huberman interactive model with triangulation to ensure validity. Findings – The study found that humanistic supervision transformed teachers' attitudes from passive and anxious to open and reflective. Teachers designed differentiated lesson plans responsive to students’ cognitive and sensory needs, utilized multisensory media (such as braille cards, tactile props, and interactive audio), and conducted functional assessments. A collaborative professional culture emerged, shown through regular reflective forums and peer learning. Student engagement also improved, marked by greater participation and communication confidence, especially among students with disabilities. Research Implications – The study highlights the importance of adopting humanistic, reflective supervision models that position teachers as learning partners. Such approaches can strengthen inclusive practices and improve learning quality in special education contexts, offering a transformative alternative to conventional evaluative models.